TKJ Laboratory Inventory Monitoring System Using Web-based AHP (Analytical Hierarchy Process) Method at SMK Negeri 1 Doko - Budi Prasetyo; Dimas Fanny Hebrasianto Permadi (Universitas Muhammadiyah Sidoarjo, 2021)
Reporting and collecting data on inventory tools using the old method does not rule out the possibility of data reporting errors and determining priorities for procurement of laboratory inventory at SMK Negeri 1 Doko. The development of increasingly advanced technology requires computerized inventory data collection, which is expected to reduce paper use, so that checking inventory conditions can be easy and efficient. To make it easier to determine the procurement of inventory, a system is needed that can make it easier to determine the priority of inventory procurement and is expected to help problems in MK Negeri 1 Doko. Therefore, research will be carried out with the aim of making it easier to monitor and determine priorities for laboratory inventory procurement. This research is a development research using the waterfall method using the AHP algorithm for system development. The results showed that the results obtained from testing the AHP calculation manually or using the application obtained that there were several values ​​that had a difference of 0.000001 the consistency ratio showed less than 10%. It could be concluded that the AHP calculation was still acceptable. BlackBox testing and beta testing the user satisfaction level of 88.25% indicates that the monitoring application system built is acceptable and can run according to its function.